Asertif Komunikasi Merubah Pilihan untuk KB Rasional - Laili, Fitria Jannatul (JURNAL KEBIDANAN BESTARI, 2022)
Many clients (Women’s who in Reproductive Age) in choosing a family planning method were not in accordance with rational family planning. The clients prefered to use of 3 (three) month’s injectable birth control that containing only the progestin hormone. 3 (three) months injectable birth control had several side effects including that it could increase body weight. This side effect could be felt by anyone. This was a midwife's challenge in overcoming or providing solutions to clients without offending, patronizing, or imposing the midwife's will. Therefore, midwives could perform assertive communication techniques in assisting clients in choosing a family planning method that suits the client's needs but still focusing on achieving that the client could choose a rational family planning method in accordance with government programs. Keywords: Assertive Communication, Rasional